2011
DOI: 10.5194/acp-11-9503-2011
|View full text |Cite
|
Sign up to set email alerts
|

The Eyjafjöll explosive volcanic eruption from a microwave weather radar perspective

Abstract: Abstract. The sub-glacial Eyjafjöll explosive volcanic eruptions of April and May 2010 are analyzed and quantitatively interpreted by using ground-based weather radar data and the Volcanic Ash Radar Retrieval (VARR) technique. The Eyjafjöll eruptions have been continuously monitored by the Keflavík C-band weather radar, located at a distance of about 155 km from the volcano vent. Considering that the Eyjafjöll volcano is approximately 20 km from the Atlantic Ocean and that the northerly winds stretched the plu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…When the observation is close to the volcano vent, remote sensing instruments can be used to estimate the near-source eruption parameters. The most important near-source parameters are the plume height and the tephra eruption rate and mass Marzano et al, 2011;Vulpiani et al, 2011;Maki et al, 2012). The retrieval of these parameters represents an important input for Lagrangian ash dispersion models, which are used to predict the geographical areas likely to be affected by significant levels of ash concentrations (Webley and Mastin, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When the observation is close to the volcano vent, remote sensing instruments can be used to estimate the near-source eruption parameters. The most important near-source parameters are the plume height and the tephra eruption rate and mass Marzano et al, 2011;Vulpiani et al, 2011;Maki et al, 2012). The retrieval of these parameters represents an important input for Lagrangian ash dispersion models, which are used to predict the geographical areas likely to be affected by significant levels of ash concentrations (Webley and Mastin, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On 16 April only one estimate is presented because of the unfavourable satellite's swath characteristics. The highest measured heights by a radar located at Keflavik airport (Marzano et al, 2011) are shown for the comparison. Please note that the radar height only reflects the eruption column height near the vent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 9 contains also the ACTH estimations from ground radar measurements at Keflavik airport (see Fig. 5 in Marzano et al, 2011). Both datasets show that ACTH tends to get lower over time as the eruption intensity decreases.…”
Section: Case Study: Eruption Of Eyjafjallajökull In April 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…Also the French Service des Avions Français Instrumentés pour la Recherche en Environnement (SAFIRE) ATR 42 and Falcon20 aircrafts, the British Facility for Airborne Atmospheric Measurements (FAAM) BAe146 and Natural Environment Research Council (NERC) Dornier Do228 aircrafts, the Netherlands National Aerospace Laboratory (NLR) Citation II aircraft, the Swiss METAIR Dimona motor glider, the Spanish CASA 212 aircraft and a number of smaller aeroplanes conducted measurement flights over Europe during the 2010 Eyjafjallajökull eruption. Microwave weather radars were used as well to study the eruption (Marzano et al, 2011).…”
mentioning
confidence: 99%